Advancing sustainability through multifunctional landscapes: beyond soil and water conservation - Kumar, Gopal (Indian Society of Agricultural Engineers, 2025)
India, with its vast and diverse landscapes, faces critical challenges of land degradation, biodiversity loss, and climate vulnerability. Transitioning from conventional soil and water conservation efforts to multifunctional landscapes provides an integrated solution by combining conservation, regeneration, wetlands, and agroecology. This article examines India’s experience with watershed programs, their successes and limitations, and highlights the potential of multifunctional landscapes to address complex socio-ecological challenges while enhancing resilience and livelihoods.